2014
DOI: 10.1063/1.4891869
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study of CO-induced segregation in gold-based alloys

Abstract: This paper reports a systematic study of the effect of CO gas on the chemical composition at the surface of gold-based alloys. Using DFT periodic calculations in presence of adsorbed CO the segregation behavior of group 9-10-11 transition metals (Ag, Cu, Pt, Pd, Ni, Ir, Rh, Co) substituted in semi-infinite gold surfaces is investigated. Although, CO is found to be more strongly adsorbed on (100) than on the (111) surface, the segregation of M impurities is found to be more pronounced on the (111) surface. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…are still in excellent agreement with ours due to a cancellation of the over-binding when the difference is taken between CO bound on a host and SAA material [32].…”
Section: Co Segsupporting
confidence: 79%
See 3 more Smart Citations
“…are still in excellent agreement with ours due to a cancellation of the over-binding when the difference is taken between CO bound on a host and SAA material [32].…”
Section: Co Segsupporting
confidence: 79%
“…This has previously been noted experimentally for dilute Pd/Cu SAA nanoparticles whereby exposure to CO pulls Pd to the surface and consequently enhances the activity of these nanoparticles towards acetylene hydrogenation [26]. Moreover, several theoretical studies have demonstrated the phenomenon of adsorbate induced segregation [27][28][29][30][31][32][33]. For example a study by Sansa et al on the CO induced segregation of single transition metal dopant atoms in Au reveals that the adsorption energy of CO is sufficient to promote dopant atom segregation to both the Au(111) and Au(100) surfaces from the bulk [32].…”
Section: Co Induced Surface Segregationmentioning
confidence: 96%
See 2 more Smart Citations
“…The CO adsorption is a driving force for Pd preferential surface segregation on Au/Pd(111) [4,5] and induces migration of Cu on top of Cu/ Pt(111) generating a stable CO/CuPt surface alloy [6]. The COinduced surface segregation energies for gold-based alloys with transition metals (Ag, Cu, Pt, Pd, Ni, Ir, Rh, Co) are calculated by the density functional theory (DFT) [7]. An efficient segregation of Cu is demonstrated in Ag/Cu(100) alloy due to adsorption of O 2 [8].…”
Section: Introductionmentioning
confidence: 99%